2021
DOI: 10.3390/instruments5020020
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Requirements in Time Resolving Tracking for Astroparticle Experiments in Space

Abstract: A large-area, solid-state detector with single-hit precision timing measurement will enable several breakthrough experimental advances for the direct measurement of particles in space. Silicon microstrip detectors are the most promising candidate technology to instrument the large areas of the next-generation astroparticle space borne detectors that could meet the limitations on power consumption required by operations in space. We overview the novel experimental opportunities that could be enabled by the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
(103 reference statements)
1
8
0
Order By: Relevance
“…A case-of-study simulation of an instrument composed of an upstream tracker made of 10 SiMS layers with time resolution of 100 ps and a downstream homogeneous BGO calorimeter has been setup to verify the advantages. The results, detailed in [3], confirmed that in a layout of telescopic AP detectors the identification of hits from back-scattered particles in the tracker and e/p separation based on tracker standalone information can be enabled by time information in addition to the 3D position and charge measurement with SiMS in space (Figure 1).…”
Section: Opportunities Of 5d Tracking For Cosmic Ray Space Detectorssupporting
confidence: 56%
See 3 more Smart Citations
“…A case-of-study simulation of an instrument composed of an upstream tracker made of 10 SiMS layers with time resolution of 100 ps and a downstream homogeneous BGO calorimeter has been setup to verify the advantages. The results, detailed in [3], confirmed that in a layout of telescopic AP detectors the identification of hits from back-scattered particles in the tracker and e/p separation based on tracker standalone information can be enabled by time information in addition to the 3D position and charge measurement with SiMS in space (Figure 1).…”
Section: Opportunities Of 5d Tracking For Cosmic Ray Space Detectorssupporting
confidence: 56%
“…Si-tracking sensors with hit time resolutions of O(100 ps) will provide, independently from the specific implementation, a breakthrough technology for tracking in space. Unprecedented opportunities will be in fact enabled equipping AP experiments with a sub-detector featuring novel capabilities while keeping similar weight and dimension budgets, such as (see [3] for details):…”
Section: Opportunities Of 5d Tracking For Cosmic Ray Space Detectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Timing information in the tracker could be measured with a spatial granularity down to O(1 cm 2 ) (as opposed to the O(100 cm 2 ) of the plastic scintillator ToF), opening the opportunity for a combined trajectory and timing measurement at the level of single particle even in the harsh environment of high hit occupancy in the tracker due to large back-scattering from the calorimeter. The timing capability will thus allow to identify energy deposits in the tracking planes due to back-scattering particles from the calorimeter and to pile-up from cosmic rays (i.e., two primary cosmic rays impinging the detector inside the same trigger and FEE sampling time window), consequently improving the overall tracking reconstruction efficiency and identification capabilities of the apparatus [148].…”
Section: Timing Layersmentioning
confidence: 99%